Intrinsic T‐ and B‐cell defects impair T‐cell‐dependent antibody responses in mice lacking the actin‐bundling protein L‐plastin. Issue 7 (18th May 2013) - Todd, Elizabeth M.; Deady, Lauren E.; Morley, Sharon Celeste
<x xml:space="preserve">Abstract</x> Germinal center development, critical for long‐term humoral immunity, requires the trafficking of T and B lymphocytes to defined tissues and locations after antigenic challenge. The molecular mechanisms that support lymphocyte trafficking through the linkage of extracellular chemotactic and adhesive cues to the actin cytoskeleton are not yet fully defined. We have previously identified the actin‐bundling protein L‐plastin (LPL) as a requisite intermediary in both naive B and T lymphocyte migration and in T‐cell activation. We tested the hypothesis that humoral immunity would require LPL. We show that mice lacking LPL demonstrated defective germinal center formation and reduced production of T‐cell‐dependent antibodies. T cells from LPL−/− mice exhibited defective expansion of the follicular helper T population. Reduced expansion of LPL−/− follicular helper T cells correlated with impaired trafficking to or retention of cells in the spleen following challenge, highlighting the importance of initial lymphocyte recruitment to the eventual success of the immune response. Furthermore, LPL−/− B cells demonstrated cell‐intrinsic defects in population expansion and in differentiation into germinal center B cells. LPL thus modulates both T‐ and B‐cell function during the germinal center reaction and the production of T‐cell‐dependent antibody responses.